THE USE OF ISTI'ARAH MAJAZ IN THE QUR'AN: Study of the Tafsir of Mafatih al-Ghayb - Ichwanul Arfan; Syahrin Harahap (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
The Qur'an contains numerous verses that employ majaz isti'arah (metaphorical expressions). However, this rhetorical feature has received limited scholarly attention and is often discussed only in classical Qur'anic commentaries, particularly those emphasizing linguistic (tafsir lughawi) analysis. This study examines Fakhr al-Din al-Razi's interpretation of Qur'anic verses containing majaz isti'arah in his Mafatih al-Ghaib, while also comparing his views with those of other Muslim scholars. The objective of this research is to explore the application and interpretation of majaz isti'arah in the Qur'an based on al-Razi's exegesis. This research employs a qualitative library research approach, using the Qur'an and Mafatih al-Ghaib as the primary sources, supported by books, journal articles, and previous studies. The findings indicate that al-Razi does not extensively discuss metaphorical expressions in every relevant Qur'anic verse. Nevertheless, three representative forms of majaz isti'arah are identified in his commentary, namely isti'arah ashliyyah, isti'arah tabi'iyyah, and isti'arah makniyyah. Al-Razi's interpretation demonstrates the importance of mastering linguistic sciences, particularly balaghah, to achieve a deeper understanding of the Qur'an. This study concludes that al-Razi's rational and linguistic approach to Qur'anic interpretation remains highly relevant to contemporary studies of Ulum al-Qur'an and Qur'anic exegesis.